(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This study is a theoretical investigation of the liquid water transport coupled with moisture and heat transfer in porous polymer materials. The solid surface zeta potential and the fiber diameter are investigated to reveal the mechanisms of the coupling effects. Based on the Poisson- Boltzmann equation for electric double layers and Navier-Stokes equation of liquid flows, a mathematical model to simulate the complex coupled heat and moisture transfer in porous polymer materials is reported in this paper.